The Development of Digital Da’wah at The Indonesian Ulema Council of South Sulawesi Province - Ahmad, Amar (International Journal of Membrane Science and Technology, 2023)
Digital da’wah is a response to the dynamics of technological development in the lives of Muslim communities. The proselytizers are transforming and adapting from the phenomenon of conventional da’wah to digital da’wah. This research aimed to reveal the response of the Indonesian Ulema Council (IUC) of South Sulawesi Province to the development of digital da’wah construction amidst changes in the transformation of da’wah with its various dynamics and problems. This qualitative research was conducted at the IUC of South Sulawesi Province located in Makassar. The approach in this research was interdisciplinary by looking at the phenomenon of society and proselytizers conveying their da’wah via digital. The data source was obtained from the IUC of South Sulawesi Province website at https://muisulsel.or.id/ and the researcher conducted interviews with core administrators such as the general chairman, secretary general, commission for da’wah and Islamic community development, and communications and informatics commission at the IUC of South Sulawesi Province. The finding of this research revealed that the IUC of South Sulawesi Province has innovated in responding to technology through digital da’wah. The progress of digital da’wah allowed the IUC of South Sulawesi Province to explain Islamic messages to individual believers and groups so that they reminded each other and connected in accessing digital da’wah. The digital da’wah phenomenon at IUC of South Sulawesi Province referred to the use of digital technology and online platforms to spread religious messages and Islamic da’wah. The IUC of South Sulawesi Province was developing digital da’wah. The digital da’wah developed by the IUC of South Sulawesi Province consisted of six forms, including social media, podcasts and streaming video, da’wah communication websites, live streaming, social campaigns and activism, as well as e-books and digital publications. The idea of developing digital da’wah carried out by the IUC of South Sulawesi Province raised the hope that the proselytizers would be able to reach all groups in spreading divine and prophetic messages. The perfection of digital da’wah also needed to be developed as ideally as possible, such as by adding aspects of Islamic media applications, da’wah applications, and online Islamic learning platforms.